A scoping review of empirical research on executive functions and game intelligence in soccer - Haugan, Jan Arvid; Lervold, Kathrine; Kaalvik, Hilde; Moen, Frode (Frontiers in Psychology, 2025)
IntroductionExecutive functions (EFs)—including working memory, cognitive flexibility, inhibitory control, and planning—are essential for adaptive decision-making in dynamic environments like elite soccer. This scoping review explores the relationship between EFs and game intelligence in adult elite soccer players.MethodsA systematic search was conducted across six major databases: Scopus, Web of Science, SportDiscus, PubMed, PsycInfo, and ERIC. Fifteen peer-reviewed empirical studies published between 2000 and 2023 were identified and analyzed for inclusion.ResultsThe review reveals a strong association between EFs and players’ ability to process complex game situations, anticipate opponents’ actions, and make strategic decisions under pressure. Evidence also points to possible variations in EF demands across playing positions. Additionally, several studies suggest that EFs may be trainable through perceptual-cognitive interventions, although this area remains underexplored.DiscussionDespite promising findings, the studies exhibit substantial methodological heterogeneity, particularly in the operationalization of both EFs and game intelligence. This variability limits the comparability and generalizability of results. The review underscores the need for more standardized methodologies, longitudinal research designs, and integrative approaches that account for both cognitive and personality factors to better understand elite soccer performance.